PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI LOGAM DAN SEJENISNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2007-2011 - Zulkifli Zulkifli; Yuli Antina Aryani (Jurnal ACSY : Jurnal Accounting Politeknik Sekayu, 2016)
The purpose of this study to identify and analyze whether Return On Asset (ROA), Return On Equity (ROE), Earnings Per Share (EPS) and Net Profit Margin (NPM) simultaneously and partially effect to the stock price on the metal and allied industry companies listed at Indonesia Stock Exchange. Population and sample in this study is the metal and allied companies’ financial statements listed at Indonesia Stock Exchange in 2007-2011. The data used is panel data. The analysis technique used is the descriptive statistic analysis, data quality tests, and multiple linear regression tests. Based on the test results, it can be concluded that Return On Asset (ROA), Return On Equity (ROE), Earnings Per Share (EPS) and Net Profit Margin (NPM) simultaneously effect significant to stock price. Partially Return On Asset (ROA) does not effect and positive to stock price, Return On Equity (ROE) and Net Profit Margin (NPM) effect negative and significant to stock price, while Earnings Per Share (EPS) effect positive and significant to stock price. Advice given is the management company should be able to manage assets and equity held better, as well as net sales must be balanced with cost efficiency. For next researcher are expected to develop the scope of the study and add variables of the study.